Does integrated health management within a county medical consortium improve rural type 2 diabetic patients' self-management behavior and quality of life? An empirical analysis from Eastern China - Mingyao Peng; Li Li; Xinyi Shi; Zhonghua Wang (BMC, 2024)
Abstract Background Levels of self-management behaviors (SMB) and quality of life (QoL) are suboptimal in Chinese adults with type 2 diabetes (T2D), especially in rural China. Integrated health management within a county medical consortium, featuring multi-level teams of doctors, nurses, and other professionals offering follow-up services such as check-ups, assessments, treatment, and health education, is promising in improving this. This study aimed to assess the effect of integrated health management within a county medical consortium on the SMB and QoL of rural T2D patients in China. Methods Based on a survey conducted on the county medical consortium in Eastern China, this study initially employed propensity score matching (PSM), a nonparametric technique, to precisely estimate the average treatment effect on the treated (ATT) of integrated health management on SMB and QoL in rural T2D patients. Subsequently, quantile regression was also performed to estimate the relationship between the implementation of integrated health management, sociodemographic factors, follow-up services (offered during integrated health management) and both SMB and QoL. Results The ATT values for SMB and QoL, representing the net effect of integrated health management within a county medical consortium on SMB and QoL, were significantly positive. They ranged from 4.34 to 4.67 for SMB and from 0.89 to 1.06 for QoL, respectively, based on the four different PSM modalities. The results of quantile regression also revealed a statistically significant positive association between the implementation of integrated health management and both SMB (coef. = 4.15) and QoL (coef. = 1.54). These findings suggest that integrated health management within a county medical consortium can effectively improve SMB and QoL in rural T2D patients. Furthermore, frequency of follow-up service and health behavior guidance were positively associated with SMB and QoL. Conversely, on-call follow-up services, medication guidance and follow-up services at medical institutions were negatively correlated with SMB or QoL. Conclusions The study highlights the effectiveness of integrated health management within a county medical consortium in improving SMB and QoL among individuals with T2D in rural China. The findings offer invaluable insights for the advancement of chronic disease management in rural areas of developing countries.